2018
DOI: 10.2320/matertrans.m2017406
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Behavior and Its Effects on Mechanical Properties in a Pre-Twinned Mg–6Al–1Zn Alloy

Abstract: In the present study, an extruded Mg6Al1Zn alloy was pre-compressed along extrusion direction to generate sufficient tensile twins. Afterward, the pre-twinned samples were annealed at 170°C for aging. Precipitation of the second-phase particles was found to preferentially occur in twins and twin boundaries. The precipitation phase is proved to be Al 12 Mg 17 . Moreover, precipitation behaviors in the two twin boundaries on both sides of every twin were very different: a considerable number of second-phase part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In magnesium alloys, it is found that the existence of pre-strain is beneficial for precipitation of the second-phase particles. If a sample without pre-strain is annealed at 170 • C or a slightly higher temperature, no obvious strengthening effect is observed [14][15][16]. It is deduced that the inner stress induced by pre-strain may have effects on precipitation of the second-phase particles.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In magnesium alloys, it is found that the existence of pre-strain is beneficial for precipitation of the second-phase particles. If a sample without pre-strain is annealed at 170 • C or a slightly higher temperature, no obvious strengthening effect is observed [14][15][16]. It is deduced that the inner stress induced by pre-strain may have effects on precipitation of the second-phase particles.…”
Section: Discussionmentioning
confidence: 94%
“…It is reported that pre-deformation has an obvious influence in precipitation behavior in magnesium alloys. Our previous work [14] had found that there were a few precipitates appearing in the AZ61 alloy during annealing if the alloy was not subjected to pre-deformation. However, if the alloy was subjected to pre-deformation and then annealed under a relatively low temperature, a higher quantity of second-phase particles, for instance, Al 12 Mg 17 , would appear in the alloy.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This indicates that the solute atoms will be more active during the heat treatment combined with loading, thus leading to enhanced precipitation during aging. Our previous study [17] also reported that the pre-strain could promote the second-phase nucleation during the subsequent annealing owing to the internal stress in the pre-strained alloy. As the applied stress was lower than the yield stress in this study, no dislocation gliding and twin nucleation occurred in the alloy during the simultaneous annealing and loading.…”
Section: Microstructural Evolution As a Function Of The Annealing And...mentioning
confidence: 88%
“…This indicates that the solute atoms will be more active during the heat treatment combined with loading, thus leading to enhanced precipitation during aging. Our previous study [17] also reported that the pre-strain could promote the second-phase nucleation during the subsequent annealing owing to the internal stress in the pre-strained alloy.…”
Section: Microstructural Evolution As a Function Of The Annealing And...mentioning
confidence: 88%